Compras 4.0: um estudo de caso múltiplo da indústria 4.0 no processo de compras industriais - Sirtori, Guilherme (My University, 2019)
Industry has always been an important link in the development of humanity. The search for means of production that make life easier for human beings, coupled with the profit it provides, has continually motivated the improvement of industries. Combined with new technologies, it has also set great milestones in the transition of manufacturing processes called revolutions. The first of these occurred through mechanization with steam and coal machines. The second brought the first concepts of mass production and assembly line, fueled by oil and electricity. In the third, production was automated using computers and robots. Finally, on Wednesday, production was connected and became intelligent, with machines talking to each other, to humans, making decisions and collecting a plethora of data throughout the process, here is “industry 4.0”. In this context, the ways in which many industrial activities take place are undergoing a new transformation and the need arises to understand how the processes of companies, such as their different departments, are behaving in the face of the fourth industrial revolution. Thus, the objective of this project is to analyze how the components and principles of industry 4.0 may be present in the purchasing processes of a Brazilian business segment. To this end, the study included the four companies with the highest revenue affiliated to the Union of Mechanical, Metallurgical and Electrical Material Companies of Caxias do Sul and region (SIMECS). In order to achieve this objective, it was decided to develop an applied research, with a qualitative approach and exploratory-descriptive objectives, outlined through a multiple case study. A script of semi-structured interviews was prepared and applied to the purchasing professionals of the referred industrial segment. As a criterion of study quality, reports, direct observation and documentary research were triangulated. The analysis of these data was performed using NVivo software, a tool that allows the application of the content analysis interpretation method, and Microsoft Excel software, which supported the tabulation of data and its transformation into graphic format to facilitate the exposure of the data that was analyzed. Finally, this project sought to complement the scientific knowledge already evidenced in the area of corporate purchasing, and thus, enable its evolution by following the cutting edge of industrial development with regard to its processes, industry 4.0. The results found from this analysis allowed the development of the proposed conceptual scheme, a functional activity flowchart, which identified possible interactions between components and, above all, industry 4.0 principles with the purchasing sector activities. These evidenced the real possibility of automating processes by adopting a vision focused on industry 4.0 principles for parameterization of elements already present in their daily lives, without the need for large investments. Thus, opportunities for improvement in processes, tools, records and actions were presented by deepening the application of this concept, called Purchasing 4.0.
A indústria sempre foi um importante elo no desenvolvimento da humanidade. A busca por meios de produção que facilitem a vida dos seres humanos, aliada ao lucro que isso proporciona, motivou continuamente o aprimoramento das indústrias. Combinada à novas tecnologias, também determinou grandes marcos na transição dos processos de manufatura, denominadas revoluções. A primeira delas ocorreu através da mecanização, com as máquinas a vapor e carvão. A segunda trouxe os primeiros conceitos de produção em massa e linha de montagem, alimentada pelo petróleo e eletricidade. Na terceira, a produção foi automatizada, utilizando computadores e robôs. Finalmente, na quarta, a produção foi conectada e se tornou inteligente, com máquinas conversando entre si, com os seres humanos, tomando decisões e coletando uma infinidade de dados em todo processo, eis a “indústria 4.0”. Nesse contexto, as formas que muitas atividades industriais ocorrem estão passando por uma nova transformação e surge a necessidade de compreender como os processos das empresas, tais quais seus diferentes departamentos, estão se comportando frente à quarta revolução industrial. Assim, o objetivo desta dissertação é analisar como os componentes e princípios da indústria 4.0 podem estar presentes nos processos de compras de um segmento de empresas Brasileiro. Para tal, participaram do estudo as quatro empresas de maior faturamento filiadas ao Sindicato das Empresas Mecânicas, Metalúrgicas e de Material Elétrico de Caxias do Sul e região (SIMECS). Para o alcance desse objetivo, optou-se pelo desenvolvimento de uma pesquisa de natureza aplicada, com abordagem qualitativa e objetivos exploratório-descritivos, delineados através de um estudo de múltiplos casos. Foi elaborado um roteiro de entrevistas semiestruturadas e aplicadas junto aos profissionais de compras do segmento industrial referido. Como critério de qualidade do estudo, foram triangulados relatos, observação direta e pesquisa documental. A análise desses dados foi efetuada por meio do software NVivo, ferramenta que permite aplicar o método de interpretação de análise de conteúdo, e do software Microsoft Excel, o qual apoiou na tabulação de dados e transformação dos mesmos em formato gráfico para facilitar a exposição do que foi analisado. Por fim, essa dissertação buscou complementar os conhecimentos científicos já evidenciados na área de compras empresariais, e assim, possibilitar sua evolução por meio do acompanhamento da vanguarda do desenvolvimento industrial no que tangem seus processos, a indústria 4.0. Os resultados encontrados a partir desta análise permitiram o desenvolvimento do esquema conceitual proposto, um fluxograma funcional de atividades, que identificou interações possíveis entre componentes e, sobretudo, princípios da indústria 4.0 com as atividades do setor de compras. Nelas, se evidenciou a possibilidade real de automatizar processos através da adoção de uma visão com foco nos princípios da indústria 4.0 para parametrização de elementos já presentes em seu cotidiano, sem a necessidade de investimentos vultuosos. Deste modo, foram apresentadas oportunidades de melhoria em processos, ferramentas, registros e ações por meio do aprofundamento da aplicação desse conceito, denominado Compras 4.0.
Keywords: Compras; Indústrias; Revolução industrial; Shopping; Industries; Industrial revolution